Pengaruh Personal Cost of Reporting, Intensitas Moral, dan Job Satisfaction terhadap Intensi Whistleblowing pada Organisasi Perangkat Daerah (OPD) Kota Bukittinggi - Annisyah, Tiara; Helmayunita, Nayang (Universitas Negeri Padang, 2025)
The objective of this study is to examine the impact of the personal cost of reporting, moral intensity, and job satisfaction on the intention whistleblowing. The study was conducted in Bukittinggi City and included a population of 28 Regional Apparatus Organisation (OPD). A total of 128 samples were gathered for analysis. The sample approach employed was purposive sampling. The data gathering approach employed questionnaires that were distributed in person. The study employed the data analysis technique of multiple linear regression (OLS) and t-statistic testing. The findings of this study demonstrate that the personal cost of reporting, moral intensity, and job satisfaction positively and significantly influence the intention of finance personnel in the Regional Apparatus Organisation (OPD) in Bukittinggi City to engage in whistleblowing.